EXCHANGE RATE VOLATILITY AND PERFORMANCE OF MICRO AND SMALL ENTERPRISES IN SOUTHEAST, NIGERIA (Journal of Global Accounting, 2025)
This study investigated the impact of macroeconomic variables on the performance of Micro and Small Enterprises (MSEs) across various sectors, utilizing a sample of 450 respondents. The primary objective was to analyse how macroeconomic factors such as gross domestic product (GDP) growth, exchange rates, interest rates, central bank exchange rate policies, and government debt influence customer satisfaction and market expansion among micro and small enterprises. To achieve this, the study employed the econometric regression technique of Ordinary Least Squares (OLS) across five models, each incorporating different macroeconomic variables as predictors. The first model examined the relationship between GDP growth and enterprise performance, yielding a positive and statistically significant coefficient of 0.45 (p < 0.01), indicating that higher economic growth enhances SME customer satisfaction and market reach. The second model assessed the influence of exchange rates, which showed a negative coefficient of -0.32 (p < 0.05), suggesting that currency depreciation adversely affects SME performance by increasing operational costs. The third model focused on interest rates, revealing a negative coefficient of -0.27 (p < 0.05), implying that rising interest rates hinder SME growth by elevating borrowing costs. The fourth model incorporated central Bank exchange rate policies, which exhibited a modest negative relationship with SME performance, with a coefficient of -0.15 (p > 0.05), indicating limited significance. The fifth model analyzed government debt, resulting in a negative coefficient of -0.40 (p < 0.01), emphasizing that high public debt levels can crowd out private sector growth and negatively impact SMEs. The findings collectively suggest that macroeconomic stability - characterized by sustainable GDP growth, stable exchange rates, low interest rates, controlled inflation, and manageable government debt - is crucial for fostering a conducive environment for SME development. Notably, among all variables, GDP growth and government debt emerged as the most significant predictors of enterprise performance. Based on these results, policy recommendations are made.
Keywords: Central Bank Exchange Rate Policies; Exchange Rates, Government Debt; Gross Domestic Product (GDP); Interest Rates; Micro and Small Enterprises; Nigeria